Enhancing patient-provider encounters when proposing SDF therapy by utilizing a qualitative analysis of parental feedback - Crystal, Yasmi O.; Jang, Jenny Hiyeji; Raveis, Victoria H. (Frontiers in Oral Health, 2024)
PurposeSilver Diamine Fluoride (SDF) is a minimally invasive option for caries arrest, part of a paradigm shift in the management of pediatric dental caries. The perspective of parents regarding the long-term pros and cons of this therapy should be understood in order to achieve optimal patient-centered care.MethodsThis study used Constant comparative analysis as an analytic approach, applying the Precaution-Adoption Process Model (PAPM) as the Grounded Theory framework in the qualitative analysis of 30 parental unformatted, spontaneous comments collected at the end of a questionnaire to evaluate their satisfaction with treatment provided at a University Clinic.ResultsOur analysis provided important insights about the factors that influenced the parents’ decision to act and have their child receive SDF therapy, their perception of the outcomes, the necessary follow-ups after the therapy, and what impacted on their overall satisfaction with the completed procedure. Both positive and negative themes were identified. The positive themes point to SDF treatment's ease of application and addressing the immediate treatment needs on children with limited cooperation. The negative themes identified the adverse consequences of SDF treatment, specifically, the duration and appearance of the cosmetic consequences, as well as the parents’ misunderstandings and incorrect expectations of the long-term sustainability of the treatment, which in many instances requires further interventions. It was also evident from the parents’ comments that they needed additional educational guidance on other aspects of the treatment, such as the necessity for clinical follow-ups, information that impacted parents’ overall satisfaction with the treatment their child received.ConclusionOur results highlight the need to discuss the short and long term benefits of the treatment, as well as, its short and long-term limitations. Specifically, while it is important to discuss immediate outcomes and consequences, such as the ease of treatment and the resultant staining, to ensure that parental consent for the treatment is truly well-informed, it is also important to prepare parents, when this procedure is initially proposed, of the likely need for additional oral care interventions in the future.